DIVERSE System: De Novo Creation of Peptide Tags for Non-enzymatic Covalent Labeling by In Vitro Evolution for Protein Imaging Inside Living Cells. Issue 12 (17th December 2015) - Kawakami, Takashi; Ogawa, Koji; Goshima, Naoki; Natsume, Tohru
Summary: Polypeptide-tag/small-molecule pairs for specific cellular protein labeling are useful for visualizing cellular proteins and controlling their activity. Here, we report the development of an in vitro evolution-based (poly)peptide tag identification system named the DIVERSE (Directed In Vitro Evolution of Reactive peptide tags via Sequential Enrichment) system. In this system, an extremely diverse (10 14 ) library of peptide tags, displayed by covalent attachment to their encoding cDNAs, is continuously prepared from the DNA library in a one-pot approach. Using this system, we demonstrated de novo creation of non-enzymatically covalent-labeling peptide tags for a synthetic small-molecule target from a random peptide library. Protein labeling with these tags was applicable to N- and C-terminal fusions, multiple different proteins and fluorophores, and intracellular labeling. The DIVERSE system can be used not only for the de novo creation of polypeptide tags but also sequence optimization of existing polypeptide tags from extremely diverse libraries. Graphical Abstract: Highlights: DIVERSE system for in vitro evolution of (poly)peptide tags was developed Peptide tags for non-enzymatic covalent labeling were created by the DIVERSE system The DIVERSE system can be used for sequence optimization of existing peptide tags Abstract : Kawakami et al. developed an in vitro evolution-based (poly)peptide tag identification system named the DIVERSE (Directed In Vitro Evolution of Reactive peptide tags via Sequential Enrichment) system. Using the DIVERSE system, the authors demonstrated de novo creation of peptide tags for non-enzymatic, covalent protein labeling.